Item Analysis of Cultural Art Subject: The Quality and Quantity of Multiple-Choice Questions and Descriptions - Ratnaningrum, Ika; Aprillya, Rhisma Dwi; Ningrum, Alya Putri Maradika (Edukasi, 2025)
The purpose of this study is to analyze and describe the quality and quantity of multiple-choice questions and descriptions in the even semester of Cultural Arts subjects for fourth-grade students at SDN Dabin I, South Tegal District, Tegal City. This study uses a research design (mix methods). The research sample comprised 144 students answers sheets. Qualitative data were examined through content validity procedures and alignment with cognitive domains, while quantitative data were analyzed using the Anates V4 software. The results of the study show that the even semester final semester assessment questions for the fourth grade of Cultural Arts subjects for the 2024/2025 school year (multiple choice and essay) are good, but they are still found in multiple-choice questions that need to be improved. It is recommended to the question preparation team to improve the questions and conduct question item analysis activities before the questions are tested to students, in order to produce more quality question items. Contribution or findings in research is to provide information to the makers of end-of-semester assessment questions so that they can improve questions that are not of good quality before being used as an evaluation tool for students.